Humanitarian response: an investigation of the City of Ekurhuleni’s strategies in resolving response challenges - Makua, Tshepo Innocent (University of the Free State, 2021)
Disasters are physical events or human activities that may lead to loss of lives or injuries, damage to properties and disruptions to the economic and social environment. However, the effects of disasters can be reduced through disaster response and effective humanitarian response strategies. This study examines the barriers the City of Ekurhuleni disaster practitioners encounter during humanitarian response operations, as well as the strategies employed to resolve the challenges and propose recommendations for ensuring efficient response in disaster relief operations. Face-to-face interviews were used to obtain data from the City of Ekurhuleni disaster practitioners. The study revealed several challenges affecting the humanitarian response operations in the City of Ekurhuleni. The major challenges associated with disaster relief operations are insufficient resources, corruption, political interference, community unrest and lack of coordination among humanitarian agencies. Strategies for efficient humanitarian response operations should include public awareness campaigns, community capacity building, proper coordination among stakeholders and strengthening the humanitarian response plans with appropriate and corresponding details of how to manage the challenges.
Dissertation (M. Disaster Management (Disaster Management Training and Education))--University of the Free State, 2021
Keywords: Disasters; Disaster response; Disaster relief operations; Humanitarian response challenges